Relational Capital Can Improve Marketing Performance With the Mediation of Dynamic Capability: A Theory of Planned Behavior Perspective - Wibisono, Dimas; Febriyanti, Novi; Marsuking, Marsuking; Dwita Nuansari, Shindy; Zulfahmi Rapi, Muh (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2024)
This study aims to determine whether relational capital can improve marketing performance with dynamic capability mediation. This research discusses relational capital with marketing performance with dynamic capabilities. SEM-PLS with Smart PLS 3.0 software is used in this study to concurrently assess the mediation effect. Through surveys, data from 200 MSMEs with a focus on the coffee industry were gathered. From January to August 2023, questionnaires were given to business managers or marketing teams in Sleman, Yogyakarta. Implications Particularly for coffee enterprises, the acceptance or rejection of hypotheses reveals management ramifications. First, organizations may be able to adjust to the environment more rapidly thanks to dynamic capability. Additionally, it can keep up with and enhance marketing. Third, it aids in the survival of app startups. In a pertinent way, Dynamic Capability conceptualizes both internal and external stakeholders.